Study of Plasmodiophora brassicae's Virulence and its Management on Cauliflower - Ghimire, P; Baral, S; Rajbhandari, R D; Pant, D; Khanal, S (Journal of the Plant Protection Society, 2022)
Club root disease is one of the most serious diseases affecting the production and the quality of cruciferous vegetables. The main aim of the study was to identify virulence of Plasmodiophora brassicae's pathotypes and assessment of efficacy of different treatments against clubroot disease. A field survey was conducted on 10 cauliflower's sample from Dhading, Makawanpur, Kavrepalanchowk, Lalitpur, Bhaktapur and Kathmandu, similarly laboratory experiment were conducted to assess the efficacy of different treatments. Disease inoculum was inoculated in 7 days old healthy seedlings of cauliflower and transplanted in the potting mixture with treatments applied. The virulence of each isolates and effectiveness of treatments along with differential hosts against clubroot was evaluated for disease incidence and severity. Isolates collected from Kavre (Panauti), Makawanpur (Palung) and Dhading (Benighat) showed highest disease incidence and severity. Similarly, Boron and Lime showed the least disease incidence and severity percentage, of 44.45% and 33.33% respectively followed by Trichoderma and Lime treatment with 48.14% and 37.03% disease incidence and severity respectively. Similarly, differential reaction among cole crops, cauliflower had highest incidence (100%) and severity (45%) followed by broccoli. While efficacy results of different treatments are derived from pot experiment so, it is needed to further validate by testing in disease infested fields.